Kepemimpinan Trump, America First, dan Nasionalisme Pertahanan: Relevansinya Terhadap Strategi Logistik dan Kemandirian TNI - Broto, Fadjar Wahyudi; Nurhidayat, I Ketut Bina S,; Nurhidayat, Nurhidayat; Tuwadi, Tuwadi; Susilo, Tarsisius (Jurnal sosial dan sains, 2025)
This study analyzes Donald Trump's leadership through the America First policy that emphasizes the protection of strategic industries, especially the defense and energy sectors, as well as its relevance for Indonesia in building logistics independence and strengthening national defense strategies. The background of this research is based on Trump's protectionist orientation that puts domestic interests above the international agenda, which practically influences global geopolitical and economic dynamics. The purpose of this research is to explore the relationship between resource nationalism and defense strategy in a global context, as well as reflect on Indonesia's needs. The research uses a qualitative approach with a case study method, combining primary data from expert interviews with secondary data in the form of academic literature, policy reports, and official documents. Key findings show that the defense and energy industry's protection policies under Trump reflect realism in international relations, while underscoring the urgency of resource nationalism in safeguarding the country's sovereignty. The America First approach has been successful in reducing the United States' dependence on energy imports and strengthening the capacity of the domestic defense industry, despite criticism of protectionism. Its relevance for Indonesia lies in the need to build a robust, adaptive, and self-sustaining defense logistics system to face the dynamics of contemporary threats, including dependence on imports of defense equipment, ammunition, and energy. The contribution of this research is to provide strategic reflection for the TNI in strengthening the Universal Defense Doctrine (Sishanta) by emphasizing the integration of national resources, the independence of the defense industry, and the development of a resilient logistics system.